2014
DOI: 10.1093/infdis/jiu646
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Disease Progression to AIDS and Death in a Rural Ugandan Cohort Is Primarily Dependent on Viral Load Despite Variable Subtype and T-Cell Immune Activation Levels

Abstract: These findings suggest that the independent contribution of T-cell activation on morbidity and mortality observed in European and North American cohorts may not be directly translated to the HIV epidemic in East Africa. In this setting, HIV-1 load appears to be the primary determinant of disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
16
1
Order By: Relevance
“…Second, it suggests that HIV subtype studies on disease progression and clinical impacts could be biased depending on the genomic region used for subtyping. For instance, numerous studies reported that subtype D infections (by pol ) as being more aggressive with a faster disease progression [2022]. However, in our current report, multiple patients had subtype D in pol , but A1 in GP41.…”
Section: Discussioncontrasting
confidence: 70%
“…Second, it suggests that HIV subtype studies on disease progression and clinical impacts could be biased depending on the genomic region used for subtyping. For instance, numerous studies reported that subtype D infections (by pol ) as being more aggressive with a faster disease progression [2022]. However, in our current report, multiple patients had subtype D in pol , but A1 in GP41.…”
Section: Discussioncontrasting
confidence: 70%
“…HIV-1 subtype A1 was predominant in the study children—representing 62.5% and 76.2% of all isolates as determined by the nef and gag sequences, respectively—followed by subtypes D and C. Some samples showed discordant subtypes between the nef and gag sequences, suggesting that the children were infected with recombinant viruses. A study in Uganda described a correlation between HIV-1 subtype D infection and rapid disease progression in adults, although HIV-1 load appeared to be the primary determinant [ 37 ]. However, our present findings indicated that subtype distribution did not significantly differ between the rapid and slow progressors.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, the predictive value of CA RNA for the response to ART has not yet been reported. Likewise, CD4 + count and plasma VL are firmly established as independent predictors of disease progression in the absence of treatment (7)(8)(9), and studies have reported an independent predictive value of total HIV-1 DNA for disease progression (10)(11)(12)(13). However, no study has directly compared plasma VL and CA HIV-1 RNA for the prediction of the rate of CD4 + T cell decline in the setting of untreated HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%